2017
DOI: 10.1186/s12955-017-0682-0
|View full text |Cite
|
Sign up to set email alerts
|

Developing a proxy version of the Adult social care outcome toolkit (ASCOT)

Abstract: BackgroundSocial care-related quality of life is a key outcome indicator used in the evaluation of social care interventions and policy. It is not, however, always possible to collect quality of life data by self-report even with adaptations for people with cognitive or communication impairments.A new proxy-report version of the Adult Social Care Outcomes Toolkit (ASCOT) measure of social care-related quality of life was developed to address the issues of wider inclusion of people with cognitive or communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 53 publications
3
59
0
2
Order By: Relevance
“…As to the latter, this might include specific commitments that individuals’ responses would be anonymised and not linked specifically to service eligibility/assessment for individuals. We outline how we subsequently embedded these features into a proxy version of the ASCOT measure in a separate paper [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the latter, this might include specific commitments that individuals’ responses would be anonymised and not linked specifically to service eligibility/assessment for individuals. We outline how we subsequently embedded these features into a proxy version of the ASCOT measure in a separate paper [51].…”
Section: Discussionmentioning
confidence: 99%
“…Two researchers (TC, JC) familiarised themselves with the transcripts, audio recordings and interview notes in order to identify key ideas and recurrent themes. Some themes were pre-defined, having been identified in the literature as potentially key issues for proxy respondents: for example, the different perspectives that proxies may adopt to answer proxy-report questions, and the acceptability of being a proxy [46, 50]. Other themes emerged through the data.…”
Section: Methodsmentioning
confidence: 99%
“…Malley et al [70] and Towers et al [67] demonstrated the feasibility of using ASCOT among older people and care home residents; however, the study also highlighted the need for proxy respondents in some situations. This later led to the development of a proxy version of the ASCOT, which demonstrated good feasibility [58]. Davis et al [30] reported that the level of agreement between patient and proxy for the EQ-5D-3L was significantly better than the level of agreement observed for the ICECAP-O in case of patients with vascular cognitive impairment.…”
Section: Validation Of Capability Instrumentsmentioning
confidence: 99%
“…Das Instrument liegt in verschie denen Versionen (zum individuellen Ausfüllen, als Beobachtungsversion) sowie in einfacher Sprache vor (Turnpenny et al 2015). Auch eine Proxy-Ver sion wurde kürzlich entwickelt, mit der andere Personen im Namen der Nutzer und Nutzerinnen sozialer Dienstleistungen antworten können (Rand et al 2017 (Forder et al 2016).…”
Section: Messung Von Lebensqualität Im Kontext Stationärer Pflegeunclassified